Distribution of near Point of Convergence, near Point of Accommodation, Accommodative Facility and Refractive Errors in a Rural Population Living in Northern Iran. Issue 3 (3rd July 2021) - Zakian, Ali; Heydarian, Samira; Mirzajani, Ali; Jafarzadehpur, Ebrahim; Yekta, Abbasali; Khabazkhoob, Mehdi
ABSTRACT: Purpose : To evaluate near point of convergence (NPC), near point of accommodation (NPA), and accommodative facility (AF) in order to determine their normative data in a rural population. Methods : The target population for this population-based, cross-sectional study was people living in rural areas. Each subject underwent extensive optometric and ophthalmic examinations, including the measurement of visual acuity, refraction, NPA, NPC, and AF. Results : The data of 1113 individuals was analyzed of whom 58.8% (n = 576) were women. The mean age of the participants was 15.26 ± 7.38 years (range: 6–30 years). The mean spherical equivalent of the subjects was 0.16 ± 0.63 D. The prevalence of myopia, hyperopia and astigmatism was 16.28% (13.97–18.58), 5.97% (4.49–7.44), 11.93% (9.91–13.95) in this study, respectively The mean and 95% confidence interval of NPC, NPA, and binocular accommodative facility (BAF) was 6.99 cm (6.84–7.15), 9.91 cm (9.71–10.11), and 9.84 cpm (9.63–10.06), respectively. A significant correlation was found between age and the parameters such that all evaluated parameters worsened significantly with age ( P < .001). Conclusion : The results of the present study showed the normal ranges of NPA, NPC, and BAF in a 6–30 year-old population living in rural areas of northern Iran. These parameters changed significantly with age.